Application Of Qur'an Murottal Therapy To The Level Of Insomnia In The Elderly In The Working Area Of Kedawung Health Center 1 - Wijayanti, Tiwik Tri; Husain, Fida' (International Journal of Health Sciences, 2023)
Insomnia is a condition in which a person has difficulty getting to sleep or maintaining sleep, or an inability to sleep with marked difficulty sleeping at night for 1 month. Non-pharmacological therapy that can be done by giving Al-Qur'an murottal therapy because it does not cause side effects and provides a relaxing effect on peace of mind, thereby reducing the level of insomnia and psychological disorders. This study aims to understand the impact of Murottal Al-Qur’an therapy on the rate of insomnia in the elderly. This research method uses case studies and descriptive research using pretest and posttest questionnaires. In this case study, researchers used Murottal Al-Qur’an Therapy to see a decrease in the rate of insomnia over 2 weeks (frequency: 6 times). Based on the results of the level of insomnia obtained by the researcher regarding the administration of Al-Qur'an Murottal Therapy to Mrs. S, the level of insomnia dropped to 10 (mild insomnia). While the measurement results showed Mr. S, the level of insomnia dropped to 13 (Mild insomnia). The results of the development of the level of insomnia before and after the application of Al-Qur'an murottal therapy were a decrease in the level of insomnia in Mrs.S and Mr.S. The results of the final comparison between the two respondents, Mrs. S and Mr. S, showed that there were differences in the causal factors. There was a significant decrease in the rate of insomnia in the elderly after being given Murottal Al-Qur’an therapy using audio.